Enhancing Students' Reading Comprehension Achievement by Using Patterned Partner Reading Strategy - Safitri, Disma Ayu; Tasnim, Zakiyah; Wahjuningsih, Eka (EFL Education Journal, 2022)
AbstractThe purpose of this study is to increase students’ reading comprehension achievement and active participation in teaching and learning reading process at SMPN 1 Kalisat by using Patterned Partner Reading strategy. The researcher used A Classroom Action Research (CAR) that had conducted one cycle where in one cycle consisted three meetings. As subject in this research was the second class with students’ number as about 38 students consist of 17 man and 21 women. Based on the research result that the students’ active participation significantly increased from 71.05 % in the first meeting to 81.57% in second meeting. The standard score from school is 75 and from the implementation the strategy, it was proved that there were 28 students or 73% of the students who achieved the target score (≥75). It means that there was the increasing of students’ reading comprehension achievement on teaching and learning process.Keywords: Partner Reading Strategy; Reading Comprehension Achievement; Students’ Active Participation; recount text